2014
DOI: 10.1538/expanim.63.73
|View full text |Cite
|
Sign up to set email alerts
|

The SNPs of Melanocortin 4 Receptor (<i>MC4R</i>) Associated with Body Weight in Beagle Dogs

Abstract: Melanocortin 4 receptor (MC4R), which is associated with inherited human obesity, is involoved in food intake and body weight of mammals. To study the relationships between MC4R gene polymorphism and body weight in Beagle dogs, we detected and compared the nucleotide sequence of the whole coding region and 3′- and 5′- flanking regions of the dog MC4R gene (1214 bp). In 120 Beagle dogs, two SNPs (A420C, C895T) were identified and their relation with body weight was analyzed with RFLP-PCR method. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
1
21
1
Order By: Relevance
“…Seong et al (2012) reported that two "silent" SNPs (g.927C>T and g.1786C>T) in the MC4R gene in Korean cattle significantly influenced marbling score and back fat, respectively. Similar results have also been reported in dogs (g.895C>T) (Zeng et al, 2014). Szyndler-Nędza et al (2013) reported that the SNP g.1426G>A in MC4R significantly affects the fat and solid content of colostrum in dam-line pigs.…”
Section: Discussionsupporting
confidence: 85%
“…Seong et al (2012) reported that two "silent" SNPs (g.927C>T and g.1786C>T) in the MC4R gene in Korean cattle significantly influenced marbling score and back fat, respectively. Similar results have also been reported in dogs (g.895C>T) (Zeng et al, 2014). Szyndler-Nędza et al (2013) reported that the SNP g.1426G>A in MC4R significantly affects the fat and solid content of colostrum in dam-line pigs.…”
Section: Discussionsupporting
confidence: 85%
“…The genotype of MC4R gene based on single nucleotide polymorphism has also been reported as genetic marker for body weight in female Beagle dogs (Zheng et al, 2014), sexual desire behavior, feed intake and finishing weight in rabbit (Fontanesi et al, 2013;El-Sabrout, 2017;El-Sabrout and Soliman, 2017), egg production in Langsan chicken (Yan et al, 2013), feed intake, body weight and ADG in yak (Cai et al, 2015), back fat thickness and marbling score in Korean cattle (Seong et al, 2012), birth body length in Kebumen cattle (Maharani et al, 2018), ADG, loin-eye area and meat quality in sheep (Zou et al, 2014) and milk production in buffalo (Deng et al, 2016). In the previous study, genetics analysis (SNPs detection, amino acid change, restriction enzyme mapping and phylogenetic tree) of MC4R gene were reported in Bligon goat (Latifah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another study, performed by Zeng et al . (), indicated that a missense substitution in MC4R (identified as 420A>C; p.Asp101Thr) was associated with body weight in Beagle dogs 12–13 months of age. Recently, it was suggested that a missense polymorphism of the GPR120 gene (c.595C>A, p.Pro199Thr) may be associated with canine obesity, given that allele frequency differed significantly when dogs with a body condition score (BCS) of 3 were compared with those with a BCS of 4 and 5 (Miyabe et al .…”
Section: Polymorphisms Identified In Tnf Il6 and Retn Genesmentioning
confidence: 99%